Prolonged time to recovery and its predictors among trauma patients admitted to the intensive care units in comprehensive specialized hospitals in Northwest Ethiopia: a multicenter retrospective follow-up study, 2022 - Messelu, Mengistu Abebe; Ayenew, Temesgen; Alamneh, Tesfa Sewunet; Demile, Tiruye Azene; Shibabaw, Aster Tadesse; Belayneh, Asnake Gashaw (Frontiers in Medicine, 2024)
A prolonged time to recovery in the intensive care units has adverse effects on both the patients and the healthcare providers. However, there is limited evidence in African countries, including Ethiopia. Therefore, this study aimed to assess the time to recovery and its predictors among trauma patients admitted to intensive care units.Methods: An iInstitutional-based retrospective follow-up study was conducted on trauma patients hospitalized in the intensive care units between January 9, 2019, and January 8, 2022. The charts of 450 patients were chosen using a simple random sampling technique. Smart phone and tabletbased data collection was done and then exported into STATA version 16 for analysis. The logrank test and the Kaplan-Meier survival curve were fitted. An adjusted hazard ratio with 95 % confidence intervals was reported to declare the strength of association between time to recovery and predictors in the multivariable Weibull regression analysis.The overall incidence density rate of recovery was 6.53 per 100 person-day observations, with the a median time to recovery of 10 days. Being on mechanical ventilation (AHR = 0.47, 95% CI: 0.34, 0.64), Glasgow Coma Scale score between 9-12 and 13-15 (AHR = 1.58, 95% CI: 1.01, 2.47, and AHR = 1.66, 95% CI: 1.09, 2.53, respectively), poly-trauma (AHR = 0.55, 95% CI: 0.39, 0.78), and presence of complications (AHR = 0.43, 95% CI: 0.31, 0.59) were significant predictors of time to recovery.The incidence rate of recovery for trauma patients is lower than the national standard, and the median time to recovery is longer. Being on mechanical ventilation, mild and moderate GCS scores, poly-trauma, and the presence of complications were significantly associated with prolonged time to recovery. Therefore, special attention has to be given for to trauma patients who had poly-trauma, complications, received mechanical ventilation, and had a lower GCS score.